'Throwing a lifeline': the role of First Link™ in enhancing support for individuals with dementia and their caregivers. (December 2012) - McAiney, Carrie A; Hillier, Loretta M; Stolee, Paul; Harvey, David; Michael, Joanne
SUMMARY Aim: The purpose of this study was to determine the extent to which First Link™, an initiative that aims to link individuals with dementia and their caregivers with support services, was able to connect caregivers of individuals with dementia to the services of the Alzheimer Society earlier in the disease process than individuals who self-refer to the Alzheimer Society, and to identify caregiver-, health professional- and health system-related impacts associated with this initiative.Participants & methods: This study evaluated First Link as implemented in two provinces in Canada and involved a mixed method, prospective cohort design; data sources included the Alzheimer Society referral database, surveys of caregivers (n = 135) and health professionals (n = 82), and interviews with key stakeholders (n = 40) and individuals with dementia and their caregivers (n = 33).Results: First Link was able to connect clients to the Alzheimer Society sooner after diagnosis compared with clients who self-referred. As a result of involvement with First Link, health professionals and caregivers had a greater capacity for managing dementia and awareness of the available community services and resources, all of which were reported to support individuals with dementia to remain at home for as long as possible and reduce failure-to-cope-related use of health system resources.Conclusion: This initiative has been well-received and is a significant approach to increasing caregiver and health professional capacity for dementia care.